Epilepsy in a Mitochondrial Disorder - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1992)
Epilepsy in 9 (22%) of 37 members of a family with maternally inherited mitochondrial disease is reported from the Department of Neurology, University Hospital, Tromsö, Norway.